Defining Democracy - Emerson, Peter. author. aut Link
XXVIII, 192 p.
Keywords: Defining Democracy looks both at the theory of why and the history of how different voting procedures have come to be used – or not, as the case may be – in the three fields of democratic structures: firstly, in decision-making, both in society at large and in the elected chamber; secondly, in elections to and within those chambers; and thirdly, in the various forms of governance, from no-party to multi-party and all-party, which have emerged as a result.